Characteristics of PVC Coated Welded Wire Mesh Fiber Reinforced Concrete - Indradi Wijatmiko; Ari Wibowo; Christin Remayanti Nainggolan (Institute of Research and Community Outreach - Petra Christian University, 2019)
Introducing fibers into concrete aims to improve the low tensile strength of concrete and its brittle properties. In this research, readily available PVC coated welded wire mesh with diameter of 1 mm was used as fibers in concrete. There are several variations of concrete samples prepared for this study, i.e. based on the fiber’s volume fraction, length and interlocking schemes. Concrete samples were subjected to tensile and compressive strength, and elastic modulus tests. The results show that the incorporation of PVC coated welded wire mesh slightly increases the tensile strength of concrete, with the optimum fiber volume fraction of 1.5%; with the fiber length of 3.6 cm, and with the interlocking of 1.2 cm. However, the concrete compressive strength is slightly reduced, compared to the normal ones. The presence of PVC coated welded wire mesh as fiber also tends to reduce the elastic modulus of fiber reinforced concrete.